Critical Success Factors Manajemen Risiko di Lembaga Pengelola Bantuan Sosial: Manajemen Risiko - A Muh Fadhil Wiguna; Dodik Siswantoro (Politeknik Ganesha Medan, 2023)
Risk management is an important thing to know, not only in the profit-oriented for private sector, but also in government and non-profit-based social institutions. Previous research has shown evidence of problems where social institutions have not yet implemented risk management while several regulatory references have been made available to improve risk management implementation. The purpose of this study is to determine the implementation of risk management and critical success factors in social management institutions. This study uses a qualitative research method with a case study approach to institutions that manage earthquake social assistance in Central Sulawesi Province in 2018. Data collection was carried out by researchers using field study methods and literature. Secondary data was obtained from internal documents, laws and regulations related to the implementation of risk management on the object of research, while primary data was collected through interviews with informants and then reduced to draw conclusions. The results of the analysis show that the object of the research has implemented risk management. Based on observations through interviews conducted with 5 (five) implementers in each institution, it shows that of the 7 (seven) critical success factors, Education and Training are critical factors in the implementation of risk management in Social Assistance Management Institutions. Strengthening the understanding of risk management for implementers can assist institutions in managing risk management better. This research is expected to provide understanding to social assistance management institutions so that risk management can be applied to prevent possible risks that may occur.